Analysis of Multicarrier PWM techniques for Photovoltaic fed Cascaded H-Bridge Multilevel Inverter - VENKATRAMAN Thiyagarajan (Journal of Electrical and Electronics Engineering, 2017)
Recently multilevel inverter technology emerging as an important alternative in the field of high power, medium voltage energy control. The various topologies for multilevel inverters such as diode-clamped, flying capacitor and cascaded H-bridge have been proposed over the years. This paper analysis the performance of a single phase seven level cascaded H-bridge inverter for photovoltaic applications. The Phase Disposition PWM (PDPWM) technique is used to generate gate signals. The performance is compared for both sinusoidal reference waveform and trapezoidal reference waveform. The analysis is carried out for different modulation index and different shading pattern of photovoltaic (PV) array. The simulation is carried out using MATLAB/SIMULINK software.